Sistem Inventory pada Toko Garuda Jaya Jakarta Berbasis Website - Juli Lidia Mariani; Harfebi Fryonanda (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
Inventory system is a system used to enter data items into a database. Based on interviews and results of research conducted with the owner of Toko Garuda Jaya Jakarta, the information contained that the system that runs on the Store's warehouse is still done manually and causes data to accumulate and data loss. Researcher aim to build an inventory system that can simplify the process of recording incoming and outgoing goods in order to make it easier for the store to get reports of incoming and outgoing goods. The final result of this research is a website-based inventory system application. The system development used is the System Development Life Cycle and Prototype Technique with the Unified Modeling Language modeling language. From the results of trials and research evaluations, the system that has been built can help stores to get data information and data reports of goods quickly and accurately.